Insulinemia and sex hormones vs. the circadian rhythm of blood pressure in women with hypertension in the postmenopausal period - Mieczkowska, Jolanta; Mosiewicz, Jerzy; Kwaśniewski, Wojciech; Rymarz, Ewa (Menopause Review/Przegląd Menopauzalny, 2012)
Introduction: Hypertension with no pressure drop during the night (“non-dippers”) is more common in postmenopausal women and contributes to increased mortality for cardiovascular reasons. Aim of the study : The aim of the study was to evaluate the relation of the circadian blood pressure profile and the profile of sex hormones, and carbohydrate metabolism in postmenopausal women with hypertension. Material and methods: In 135 postmenopausal women with hypertension, 24-hour blood pressure monitoring was performed and the blood serum concentrations of estradiol, testosterone, dihydroepiandrosterone, sex hormone-binding protein, insulin and glucose levels were determined. Results : The “dippers” group consisted of 59 patients (40.9%), and “non-dippers” group of 59 patients (40.9%) as well. The study groups did not differ in age, duration of menopause and hypertension, mean systolic and diastolic blood pressure, percentage of patients treated with beta-blocker and angiotensin converting enzyme inhibitor or rates of obesity. The studied groups of “dippers” and “non-dippers” did not differ statistically significantly in the levels of serum estradiol, testosterone, dehydroepiandrosterone sulfate and sex hormone-binding protein. In the “dippers” and “non-dippers” groups, fasting glucose levels were similar, whereas insulin levels were significantly higher in the group of “non-dippers”. Conclusions : In hypertensive women in the postmenopausal period, the circadian blood pressure profile of “non-dippers” is very common (40.9%). In postmenopausal women with high blood pressure, the profile of the “non-dippers” is accompanied by hyperinsulinemia.